2023
DOI: 10.1021/acsami.3c10579
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Dual-Action Chemo-Radio-Labeled Nanocarriers with High Efficacy against Triple-Negative Breast Cancer

Shaista Ilyas,
Sabri E. M. Sahnoun,
Annika Szymura
et al.

Abstract: Identification and selectivity of molecular targets with prolonged action for difficult-to-target cancer such as triple-negative breast cancer (TNBC) represent a persisting challenge in the precision delivery of therapeutics. In the quest to target undruggable sites, this study validates the bioavailability of polydopamine-sealed mesoporous silica nanocarriers (PDA-mSiO 2 ) for in vivo drug delivery to TNBC. For controlled transport and release, the chemotherapeutic drug doxorubicin was encapsulated in mSiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Iron oxide nanocubes were synthesized following a solvothermal reduction pathway published elsewhere. 53,54 Briefly, 0.8 g polyvinylpyrrolidone (PVP) was dissolved completely in 10 mL of N,N-dimethylformamide (DMF). PVP act as a stabilizer to regulate nucleation and growth uniformly across all axes preventing particle aggregation and kinetically controlling the growth of specific facets by binding onto others.…”
Section: Synthesis Of Iron Oxide Cubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxide nanocubes were synthesized following a solvothermal reduction pathway published elsewhere. 53,54 Briefly, 0.8 g polyvinylpyrrolidone (PVP) was dissolved completely in 10 mL of N,N-dimethylformamide (DMF). PVP act as a stabilizer to regulate nucleation and growth uniformly across all axes preventing particle aggregation and kinetically controlling the growth of specific facets by binding onto others.…”
Section: Synthesis Of Iron Oxide Cubesmentioning
confidence: 99%
“…Iron oxide nanoellipsoids were synthesized using a literature-reported method. 54 In brief, 1.3 g of iron chloride hexahydrate was dissolved in 204 mL of water with stirring until complete dissolution. To this iron chloride solution, ammonium hydrogen phosphate (13.2 mg) was added and stirred for 30 minutes to ensure complete mixing.…”
Section: Synthesis Of Iron Oxide Nanoellipsoidsmentioning
confidence: 99%
“…Diagnostic imaging is a cornerstone of modern medicine that continues to be the most frequently applied approach for dealing with a broad range of ailments and conditions. In this direction, previous studies have demonstrated the potential of solid and hollow nanocarriers (5–100 nm) for multimodal imaging using MRI, PET, SPECT, and CT techniques by enabling controlled transport, selective uptake (active targeting), and tracking (fluorophores and dyes) of drug molecules. The availability of new imaging modalities can fundamentally bring potential changes in how various cells, tissues, and organs can be visualized and treated during specific stages of a particular disease or inflammation. , The use of nanocarriers for disease administrations has shown progress due to their ability to improve drug-delivery efficacy, reduce toxicity, and enhance the specificity of drug accumulation to cells. , The improved cellular responses are linked to the advancement in the physiochemical properties of nanocarriers, bioconjugation strategies, and stimuli-responsive polymeric coatings. , The advanced drug delivery strategies apply specific functional molecules or hydrophilic polymers that offer electrostatic forces, hydrogen bonding, and π–π stacking possibilities to effectively guide and attract therapeutic agents to specific sites within the body, which consequently optimizes the outcome of medical treatments. ,, …”
Section: Introductionmentioning
confidence: 99%